Part 1
we have the equation
![\mleft|2x+1\mright|-2=3x+2](https://img.qammunity.org/2023/formulas/mathematics/college/tte9uuz5c4ap8qkql7zggz4uk0538xqvh5.png)
Solve for x
![\begin{gathered} |2x+1|=3x+2+2 \\ |2x+1|=3x+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a6bnwofd9akoemdx520y8w00mtkq7qoaj3.png)
REmember that the absolute value function has two solutions
First solution (case positive)
![\begin{gathered} +(2x+1)=3x+4 \\ 3x-2x=1-4 \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vtiyohmjlfz7zvx00l6jfk53v864rleong.png)
Second solution (negative case)
![\begin{gathered} -(2x+1)=3x+4 \\ -2x-1=3x+4 \\ 3x+2x=-1-4 \\ 5x=-5 \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hhvome32kp27rb6r3qsxk25u2dzgu5emw7.png)
therefore
the solutions are x=-3 and x=-1
Part 2
we have the function
![f(x)=-\mleft|x^3-2x^2\mright|-2](https://img.qammunity.org/2023/formulas/mathematics/college/3uiuszacu2nv88jpdu81fk9udgj4e0c5rj.png)
Remember that
f(-2) is the value of f(x) when the value of x=-2
substitute the value of x in the expression above
![\begin{gathered} f(-2)=-|-2^3-2(-2)^2|-2 \\ f(-2)=-|-8-8|-2 \\ f(-2)=-|-16|-2 \\ f(-2)=-(16)-2 \\ f(-2)=-18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uxn48xnud4ajlzidc8zn3hs0ttj8roowdm.png)